2016
DOI: 10.1186/s13045-016-0341-7
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 is upregulated by EBV-driven LMP1 through NF-κB pathway and correlates with poor prognosis in natural killer/T-cell lymphoma

Abstract: BackgroundNatural killer/T-cell lymphoma (NKTCL) is an Epstein–Barr virus (EBV)-associated, highly aggressive lymphoma. Treatment outcome remains sub-optimal, especially for advanced-stage or relapsed diseases. Programmed cell death receptor 1 (PD-1) and PD ligand 1 (PD-L1) have become promising therapeutic targets for various malignancies, but their role in the pathogenesis and their interactions with EBV in NKTCL remains to be investigated.MethodsExpression of PD-L1 was measured in NK-92 (EBV-negative) and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
193
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(204 citation statements)
references
References 59 publications
(57 reference statements)
10
193
1
Order By: Relevance
“…In addition, Green et al demonstrated that PD‐L1 in lymphoblastoid cells was up‐regulated through an LMP‐1‐mediated activation of STAT3 (signal transducer and activator of transcription 3), AP‐1 (activator protein 1), and NFκB (nuclear factor kappa B) . Furthermore, Bi et al reported that PD‐L1 was upregulated in NK/T‐cell lymphoma by an EBV‐driven activation of LMP1 and the NF‐κB pathway, and that this correlated with poor prognosis . These data indicate that EBV‐driven LMP‐1 activation could up‐regulate PD‐L1 in EBV‐positive PCNSLs, and we have previously reported that LMP‐1 gene deletion and EBV‐nuclear antigen 2 (EBNA‐2) expression are important tumorigenic factors for EBV‐positive PCNSL in immunocompetent elderly patients .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In addition, Green et al demonstrated that PD‐L1 in lymphoblastoid cells was up‐regulated through an LMP‐1‐mediated activation of STAT3 (signal transducer and activator of transcription 3), AP‐1 (activator protein 1), and NFκB (nuclear factor kappa B) . Furthermore, Bi et al reported that PD‐L1 was upregulated in NK/T‐cell lymphoma by an EBV‐driven activation of LMP1 and the NF‐κB pathway, and that this correlated with poor prognosis . These data indicate that EBV‐driven LMP‐1 activation could up‐regulate PD‐L1 in EBV‐positive PCNSLs, and we have previously reported that LMP‐1 gene deletion and EBV‐nuclear antigen 2 (EBNA‐2) expression are important tumorigenic factors for EBV‐positive PCNSL in immunocompetent elderly patients .…”
Section: Discussionmentioning
confidence: 66%
“…22 Furthermore, Bi et al reported that PD-L1 was upregulated in NK/T-cell lymphoma by an EBVdriven activation of LMP1 and the NF-κB pathway, and that this correlated with poor prognosis. 23 These data indicate that EBV-driven LMP-1 activation could upregulate PD-L1 in EBV-positive PCNSLs, and we have previously reported that LMP-1 gene deletion and EBVnuclear antigen 2 (EBNA-2) expression are important tumorigenic factors for EBV-positive PCNSL in immunocompetent elderly patients. 24 In the present study, we found no statistical difference in the number of PD-L1 TILs between EBV-positive and EBV-negative PCNSL samples.…”
Section: Discussionmentioning
confidence: 72%
“…Induction of PD‐L1 in melanoma cells is dependent on activation of NF‐κB (Gowrishankar et al, ). It has been demonstrated that NF‐κB activation contribute to LMP‐1 mediated induction of PD‐L1 in NPC cells and natural killer/T‐cell lymphoma (Bi et al, ; Fang et al, ) (Figure ). However, the relationship between PD‐L1 expression and NPC clinical outcomes is remain controversial (Li, Ding, et al, ; Zhu et al, ).…”
Section: The Pd‐1:pd‐l1 Immune Checkpointmentioning
confidence: 99%
“…An adenoviral vector-based vaccine has shown promise for targeting LMP2A, EBNA1, and, when expressed, LMP1 in nasopharyngeal carcinoma (77)(78)(79). LMP1 drives the expression of the T-cell inhibitory receptor PD-L1 (80)(81)(82), and PD-1-PD-L1 immune checkpoint blockade has improved EBV ϩ lymphoma and NPC treatment responses (19,(83)(84)(85). It will be of interest to determine whether checkpoint-blockade, perhaps together with strategies to induce EBV lytic gene expression, synergizes with adoptive immunotherapy approaches.…”
Section: Immunotherapeutic Approaches Targeting Lmp1mentioning
confidence: 99%